DEVELOPMENT OF NHT-BASED STUDENT WORKSHEETS TO TRAIN STUDENTS’ COMMUNICATION SKILLS ON REACTION RATE MATERIAL - Sudzuasmais Sudzuasmais; Bertha Yonata (UNESA Journal of Chemical Education, 2026)
The purpose of this study is to develop student worksheets based on the NHT cooperative learning model to train students’ communication skills regarding reaction rates. This Research and Development project employs the 4-D model (Define, Design, Develop), omitting the Disseminate. A limited pilot test was conducted with twelve students from Class XI-1 at Ngoro State Senior High School, Jombang in the second semester of the 2025/2026 academic year using One Shot Case Study design. The feasibility of the worksheets was assessed in terms of validity, practicality, and effectiveness. Data were collected using validation sheets, student response questionnaires, activity and oral communication observation sheets, and cognitive learning outcome tests. Validation results showed that the worksheet met valid and highly valid criteria with mode values of 3 and 4 for content and construct validity. Practicality was demonstrated by 85,71% of student response questionnaire items categorized as very positive, and 92,35% of student activities observed as very good. Effectiveness was reflected in improvements in oral communication skills; the quantity of opinion-giving increased from 50% to 58,3% and question-asking from 33,3% to 41,6%, both in the fairly good criterion. The quality of oral communication also improved, with opinion quality rising from 41,67% to 44% and question quality from 36,1% to 41,6%, both categorized as fairly good. Written communication quality across all groups reached ≥66,67%, categorized as good. All students achieved cognitive learning mastery with scores of ≥75. Thus, the developed NHT-based worksheets are suitable for training students’ communication skills on reaction rate material.